2020
DOI: 10.3390/ijms21030946
|View full text |Cite
|
Sign up to set email alerts
|

Integrative Transcriptome and Proteome Analysis of the Tube Foot and Adhesive Secretions of the Sea Urchin Paracentrotus lividus

Abstract: Echinoderms, such as the rock-boring sea urchin Paracentrotus lividus, attach temporarily to surfaces during locomotion using their tube feet. They can attach firmly to any substrate and release from it within seconds through the secretion of unknown molecules. The composition of the adhesive, as well as the releasing secretion, remains largely unknown. This study re-analyzed a differential proteome dataset from Lebesgue et al. by mapping mass spectrometry-derived peptides to a P. lividus de novo transcriptome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 72 publications
1
33
0
Order By: Relevance
“…Recently, it was confirmed that attachment of M. lignano relies on two large proteins expressed in the adhesive glands (Mlig-ap1 and Mlig-ap2; Wunderer et al, 2019). Similar transcriptomics, proteomics and expression analyses were also applied to the proseriate flatworm Minona ileanae, where nine transcripts specific to the adhesive organs were identified (Pjeta et al, 2019). Six transcripts had similar conserved domain architecture and were rich in repetitive motifs previously observed in adhesive proteins Mlig-ap1 and Mlig-ap2 of M. lignano.…”
Section: ) Platyhelminthesmentioning
confidence: 90%
See 3 more Smart Citations
“…Recently, it was confirmed that attachment of M. lignano relies on two large proteins expressed in the adhesive glands (Mlig-ap1 and Mlig-ap2; Wunderer et al, 2019). Similar transcriptomics, proteomics and expression analyses were also applied to the proseriate flatworm Minona ileanae, where nine transcripts specific to the adhesive organs were identified (Pjeta et al, 2019). Six transcripts had similar conserved domain architecture and were rich in repetitive motifs previously observed in adhesive proteins Mlig-ap1 and Mlig-ap2 of M. lignano.…”
Section: ) Platyhelminthesmentioning
confidence: 90%
“…This 108 kDa protein presents phosphorylated and glycosylated isoforms and contains six discoidin domains (similar to Sfp1) that can bind molecules bearing galactose and N-acetylglucosamine residues (Santos et al, 2013;Lebesgue et al, 2016;Toubarro et al, 2016). Recently, these proteomic data were re-mapped to a new P. lividus tube foot transcriptome (Pjeta et al, 2020). This resulted in a 60% increase in the mapped disc and stem peptides, accompanied by a 71% increase in the number of identified proteins.…”
Section: (3) Echinodermsmentioning
confidence: 99%
See 2 more Smart Citations
“…The preceding discussion suggests that the pentaradial body shape and morphological plasticity exhibited by sea stars enable them to better resist hydrodynamic loads. Sea urchins are often found in the same environment as sea stars and have a comparable biological adhesion mechanism 25 27 . Yet it is unlikely that the spiny spheroidal geometry typical of sea urchins leads to downforce generation.…”
Section: Discussionmentioning
confidence: 99%